Integrating semantic web in knowledge based institutions of higher education: issues, potentials and challenges / Sharin Sulaiman, Azlina Bujang and Azlina Narawi - Sulaiman, Sharin; Bujang, Azlina; Narawi, Azlina (Research Management Institute (RMI), 2013)
Based on Rowley (2000) he states that universities and their staff must recognize and respond to their changing role in a knowledge-based society. Universities do have a significant level of knowledge management (KM) activities, and it is important to recognize these, and use them as foundations for further development. Both public and private universities play important roles in providing easy access to knowledge especially to their students. University knowledge needs differ from corporate needs where universities seek to share scholarly knowledge for the good of society whereas corporation seeks profit However, it is also important to note that universities have started to manage knowledge as intellectual property to be sold or bartered, as well as given away (Kennedy, 1998). Realizing the benefits that KM can offers, more learning institutions have attempts to incorporate KM practices in these four main areas: learning and teaching, scholarly research, academic publishing, and libraries. However, these learning institutions face issues and limitations in practicing KM concept that need to be encountered. Among the predicaments of practicing KM concept is on an organizational knowledge management systems (KMS)still remains underutilized and hardly recognizable by knowledge workers [Davenport, 2005; Maier, 2007, McAfee, 2006]. At the same time, knowledge workers are lack in number and increasingly need appropriate Information Technology (IT) solutions facilitating their daily work [McAfee, 2006]. Therefore, in order to overcome these KM issues, it is recommended for Knowledge based institution of higher education to integrate semantic web as a way to improve the effectiveness of KM practices. In short, Web semantic is an extension of the current web in which information is given well defined meaning, better enabling computers and people to work in co-operation (Bernes-Lee,, Handier,, Lassila,. (2001). There are a number of Web-based services and applicatiohs that demonstrate the foundations of Web 2.0 concept, and they are already being used to a certain extent in the field of education. These are not really technologies per se but services (or user processes) built using the building blocks of the technologies and open standards that underpin the Internet and the Web. These include blogs, wikis, and multimedia sharing services, content syndication, pddcasting and content tagging services. Unfortunately, there are challenges exists in integrating semantic web in the institution of higher learning which relate to knowledge assets management including the availability of content, ontology availability, development and evolution, scalability, multilingualism, visualization and stability of Semantic Web languages.